Etika Tawar-Menawar Lintas Budaya: Integrasi Pragmatik dalam Pembelajaran BIPA - Grace Harzen br Perangin-angin; Anas Ahmadi; Agusniar Dian Savitri; Prima Vidya Asteria (Universitas Muhammadiyah Magelang, 2026)
This study aims to analyze the ethics of cross-cultural bargaining between Indonesia and China and its implications in learning Indonesian for Foreign Speakers (BIPA). This study employs a qualitative approach using a literature study design. The data consist of relevant scholarly articles on bargaining practices, pragmatics, and cross-cultural communication. Data were collected through documentation techniques and analyzed using data reduction, data display, and conclusion drawing. The results show that the practice of bargaining in Indonesian culture emphasizes politeness of language, indirect communication, and social harmony, while Chinese culture is influenced by the values of collectivism, the concept of guanxi, and face oriented towards social relations and reputation. These differences show that there are variations in communication strategies that are influenced by the cultural values behind them. This research emphasizes the importance of integrating pragmatic aspects and cross-cultural communication in the development of BIPA learning materials based on authentic communication.